Australian hospitality: Overseas Information Campaigns and the ‘theatricalised’ encounter - Ben Hightower (Law Text Culture, 2014)
The preface of a handbook delivered to refugees and holders of humanitarian visas currently overseas and selected for settlement in Australia ends with the words ‘Australia is a wonderful place, full of opportunities and new experiences … WELCOME TO AUSTRALIA’ (DIAC 2011).1 This handbook, given in conjunction with the Australian Cultural Orientation (AUSCO) program, is the ‘beginning of the settlement process for people coming to Australia under the Humanitarian Program’ (DIAC 2012). The ‘official welcome’ is given to each person before they ever arrive in the country. The capitalisation of ‘WELCOME TO AUSTRALIA’ at the end of the message signifies its point: ‘Be welcome here’.